2009
DOI: 10.1080/09637480903099618
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical characteristics of golden-yellow and purple-red varieties of tamarillo fruit (Solanum betaceumCav.)

Abstract: Golden-yellow and purple-red tamarillos (Solanum betaceum Cav.) cultivated in Ecuador were studied for their physical properties, proximate composition, pH, degrees Brix, acidity, sugars, organic acids, minerals, vitamin C and beta-carotene content in the edible part. Results were compared with those for Spanish fruits. The golden-yellow and purple-red Ecuadorian fruits were larger (107 and 188 g) than the respective Spanish fruits (43 and 63 g), softer but generally similar in chemical composition except for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
60
4
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 21 publications
12
60
4
6
Order By: Relevance
“…AA is a water-soluble vitamin, and it is known as an oxygen scavenger, acting as reducing agent (25). The result showed that tamarillo has high AA content as shown in Table 1.…”
Section: Beta-carotene and Ascorbic Acid (Aa) Contentsmentioning
confidence: 67%
“…AA is a water-soluble vitamin, and it is known as an oxygen scavenger, acting as reducing agent (25). The result showed that tamarillo has high AA content as shown in Table 1.…”
Section: Beta-carotene and Ascorbic Acid (Aa) Contentsmentioning
confidence: 67%
“…Consumption of fresh fruit or as juice is widespread throughout Ecuador and Andean region. Using the traditional method of preparation of fruit juices in the Andean region, the researchers found that the best antioxidant activity derived from maceration, compared with jams and jellies [18], probably as a consequence of the conservation of some natural antioxidants that, in some cases, may be lost or may decrease their properties through industrial processes. Furthermore, the insoluble matters (pomace) obtained after preparing juice showed a higher antioxidant capacity compared to when it is obtained after the industrialization process [18].…”
Section: Biological Activities and Health Effects 351 Antioxidant mentioning
confidence: 99%
“…Nevertheless, while health-related properties and chemical composition of berries commonly found in North America and Europe have been widely explored; those natives from South America need more information. Several scientific reports have pointed out the therapeutic potential of certain plants and foods from this area, for instance Rubus glaucus B., Physalis peruviana L. and Solanum betaceum C. are among the relevant ones [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Data processing was performed using MestReNova 6.2 (Mestrelab Research SL, San Diego, CA, USA). NMR spectra were recorded in DMSO-d 6 and referenced to the residual non-deuterated solvent signal at δ H 2.50 ppm. GC-FID and GC-O analyses were performed by using an HP 5890 gas chromatograph (Hewlett-Packard, San Diego, CA, USA).…”
Section: Generalmentioning
confidence: 99%
“…Some scientific studies related to the physicochemical composition, volatiles, pigment (carotenoids and anthocyanins), and polyphenol contents of this fruit have been published [4][5][6][7]. The volatile studies on red-variety fruits showed that the major constituents of pentane-dichloromethane liquid-liquid extract were methyl hexanoate, (E)-hex-2-enal, (Z)-hex-3-en-1-ol, eugenol, and 4-allyl-2,6-dimethoxyphenol [8].…”
Section: Introductionmentioning
confidence: 99%